17β-Estradiol Protects the Neonatal Brain from Hypoxia-Ischemia - Nuñez, Joseph (2007)
Hypoxia-ischemia is relatively common in human infants. Hypoxia-ischemia can occur as a result of complications associated with prematurity or birth, frequently leading to altered brain development and cognitive and behavioral deficits that persist throughout life. Despite the relative frequency of neonatal hypoxic ischemic encephalopathy, the immature brain sustains relatively less damage than an adult who experiences a similar crisis of oxygen and nutrient deprivation. Therefore, factors may be present that protect the developing brain. During late gestation, the infant brain encounters high levels of the steroid hormone 17β-estradiol. This observation, combined with evidence supporting 17β-estradiol as a neuroprotective agent, led us to hypothesize that increasing the basal level of 17β-estradiol would reduce the amount of hypoxia-ischemia induced injury to the neonatal brain. To test that hypothesis we administered 17β-estradiol using either a repeated dosing paradigm or a single dose paradigm to immature male and female rats. Here we show that the repeated dosing paradigm (three doses of 17β-estradiol) provided approximately 70% protection of the hippocampus, basal ganglia, and amygdala. By contrast, a single administration of 17β-estradiol 24 hours prior to hypoxia-ischemia conferred little protection. The only exception was the pyramidal layer of the female hippocampus, which was modestly protected (16% reduction in damage). The protection afforded by the multiple administrations of 17β-estradiol was similar for females and males, with the only exception being the male amygdala, which displayed less damage than the female amgydala. We conclude that 17β-estradiol acts as a potent neuroprotective agent against hypoxia-ischemia induced damage to the developing brain, and that pretreating infants at risk for hypoxic ischemic injury may be advisable.